2022
DOI: 10.7717/peerj.13228
|View full text |Cite
|
Sign up to set email alerts
|

Validating an inertial measurement unit for cricket fast bowling: a first step in assessing the feasibility of diagnosing back injury risk in cricket fast bowlers during a tele-sport-and-exercise medicine consultation

Abstract: This study aimed to validate an array-based inertial measurement unit to measure cricket fast bowling kinematics as a first step in assessing feasibility for tele-sport-and-exercise medicine. We concurrently captured shoulder girdle relative to the pelvis, trunk lateral flexion, and knee flexion angles at front foot contact of eight cricket medium-fast bowlers using inertial measurement unit and optical motion capture. We used one sample t-tests and 95% limits of agreement (LOA) to determine the mean differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Firstly, Holliday et al [ 20 ] calculated and reported thoracic spine orientation angle relative to the laboratory coordinate system while our thoracic spine is reported relative to the lumbar spine. Our method has been shown to be a valid approach to understanding spinal kinematics in fast bowling during cricket games [ 24 ]. Secondly, Holliday et al [ 20 ] tested participants using an ergometer in a laboratory, while our data were obtained during field-based cycling.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, Holliday et al [ 20 ] calculated and reported thoracic spine orientation angle relative to the laboratory coordinate system while our thoracic spine is reported relative to the lumbar spine. Our method has been shown to be a valid approach to understanding spinal kinematics in fast bowling during cricket games [ 24 ]. Secondly, Holliday et al [ 20 ] tested participants using an ergometer in a laboratory, while our data were obtained during field-based cycling.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing availability of low-cost wearable technology, and the establishment of robust joint-angle calculation methods, greater applications of IMUs will be realized, including remote real-time monitoring and telemedicine, particularly in the elderly and motor-compromised [ 138 , 139 , 140 ], sports training, and human performance optimization [ 141 , 142 , 143 ], defense applications such as measurement and monitoring of front-line soldiers [ 98 , 144 ], habitual motion evaluation over extended periods including in submarines and spaceflight, and film and animation applications [ 145 , 146 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the IMU-based system can measure specific cricket fast bowling movements accurately, such as the angle between the shoulder girdle and the pelvis, the bending of the trunk, and the bending of the knee. Thus, they speculated that the IMU-based system can help identify injury risk in tele-sport and exercise medicine [ 59 ].…”
Section: Cricket-related Literaturementioning
confidence: 99%